Soil and water characteristics of traditional paddy and shrimp fields of Kerala - Krishnani, K K; Gupta, B P; Muralidhar, M; Saraswathy, R; Pillai, S M; Ponnusamy, K; Nagavel, A (Indian Journal of Fisheries, 2012)
A comprehensive study was undertaken to assess soil and water quality of three different farming areas in Trichur andErnakulam districts of Kerala during traditional paddy cultivation period from June to December 2000 and the extensiveshrimp culture season from January to April 2001. Studies revealed that organic carbon in soil was higher during Pokkalipaddy crop vis a vis extensive shrimp culture. Soil was acidic during both the crops. There was no difference in other soilparameters such as electrical conductivity and redox potential. Water parameters like salinity, ammonia and nitrite valueswere marginally higher during extensive shrimp culture than during paddy crop. However, pH, chemical oxygen demand,phosphates and total phosphorous were not different between the two crops. The soil and water parameters, except soil pH,were observed to be within optimum range for shrimp farming